1998
DOI: 10.1136/bmj.317.7165.1037
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer testing as an adjunct to ultrasonography in patients with clinically suspected deep vein thrombosis: prospective cohort study

Abstract: Objective To investigate the efficacy of using a rapid plasma d-dimer test as an adjunct to compression ultrasound for diagnosing clinically suspected deep vein thrombosis. Design d-dimer concentrations were determined in all patients with a normal ultrasonogram at presentation. Repeat ultrasonography was performed 1 week later only in patients with abnormal d-dimer test results. Main outcome measure Patients with normal ultrasonograms were not treated with anticoagulants and were followed for 3 months for thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(151 citation statements)
references
References 16 publications
5
140
0
6
Order By: Relevance
“…Other management trials suggest that repeated ultrasound examinations may be safely avoided in patients with an initially negative ultrasound and a negative D-dimer test result (92,93 ). Interestingly, these studies have used various D-dimer assays from several different method categories, including second-generation latex agglutination assays (87,91 ), membrane ELISA assays (94 ), and the erythrocyte agglutination assay (55,90,92,93 ). To firmly establish the safety of these and other approaches, large trials are needed that have adequate numbers of patients at the ends of the branching pathways (95 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other management trials suggest that repeated ultrasound examinations may be safely avoided in patients with an initially negative ultrasound and a negative D-dimer test result (92,93 ). Interestingly, these studies have used various D-dimer assays from several different method categories, including second-generation latex agglutination assays (87,91 ), membrane ELISA assays (94 ), and the erythrocyte agglutination assay (55,90,92,93 ). To firmly establish the safety of these and other approaches, large trials are needed that have adequate numbers of patients at the ends of the branching pathways (95 ).…”
Section: Resultsmentioning
confidence: 99%
“…Their 3-month rate of VTE was 0.4% (CI = 0.0%-0.9%), and they reduced the volume of repeated US scans by 87%. 3 Similarly, Wells et al 14 reported that patients with low pretest probability and initially normal proximal US results (55% of patients) could forgo the repeated US at 1 week, because their 3-month rate of VTE was 0.6% (CI = 0.1%-1.8%).…”
Section: 7-10mentioning
confidence: 99%
“…This protocol will be referred to as serial proximal US. 2,3 The second protocol is one-time whole-leg, extended US (single complete US), evaluating both the proximal and distal calf infrapopliteal veins. 4,5 Serial proximal US requires repeated scanning in one week in a large number of patients with initially normal US results, most of whom will not have evidence of DVT on their repeated US.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when faced with a clinical suspicion of DVT and a need to assess the status of a thrombosed vein in order to treat its complications, specific examinations or supplementary diagnostic methods capable of directly or indirectly demonstrating the presence and extent of the thrombus must be used. Clinical prediction models such as those proposed by Wells et al 17 , in combination with laboratory D-dimer testing and imaging exams with color duplex mapping (CDM), have made it easier to reliably diagnose DVT 18,19 .…”
Section: Diagnosismentioning
confidence: 99%